IMPLEMENTASI PENDIDIKAN KARAKTER TERINTEGRASI DALAM KEGIATAN PEMBELAJARAN PADA SMK JURUSAN BANGUNAN DI DAERAH ISTIMEWA YOGYAKARTA - Jaedun, Amad; Purwaningsih, Eka; Novita, Fistian; Wiranata, M. Alwan (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The purposes of this research are to (1) identify the character values which are developed and integrated in the learning process, (2) reveal teachers’ learning strategy and its evaluation in integrating character values in the learning process, and (3) identify the obstacels among vocational high school teachers of Building department in integrating character values. This study belongs to descriptive-evaluative research which was conducted through 8 state vocational high schools of Building department in Special Region of Yogyakarta. This research was under the umbrella theme from 3 studies of the students of Civil Engineering Education and Planning Department, Faculty of Engineering UNY. The research participants were the teachers who taught the subjects of normative skills, vocational theory, and vocational practicum in Building Department of Vocational High Schools. Data collection techniques were using questionnaire, interview and documentation. Instrument validation was conducted by content validation. Data analysis technique was using descriptive analysis for both quantitative and qualitative method. The result of the research showed that (1) character values was developed differently through integration the learning process in the subjects of normative skills, vocational theory, and vocational practicum but most of them were not written in syllabus or lesson plan, (2) most of the learning strategies were generally conventional ones, which were not not written in syllabus or lesson plan as well as in the learning scenario, (3) the evaluation of character education was the weakest aspect from the implementation of integrated character education on learning process because it had not conducted appropriately yet with the integrated character values, and (4) the teacher obstacles in implementing integrated character values were especially related to the teachers’ low ability in designing, implementing, and evaluating the learning process of developed char Keywords: integrated learning of character values